Embolus Retriever with Interlinked Cages versus other stent retrievers in acute ischemic stroke: an observational comparative study. (17th May 2018) - Gruber, Philipp; Zeller, Salome; Garcia-Esperon, Carlos; Berberat, Jatta; Anon, Javier; Diepers, Michael; Nedeltchev, Krassen; Flottmann, Fabian; Fiehler, Jens; Remonda, Luca; Kahles, Timo
Abstract : Background and purpose: Given the promising performance of the new Embolus Retriever with Interlinked Cages (ERIC) in smaller case series, we sought to assess the efficacy and safety of mechanical thrombectomy (MT) with ERIC compared with other stent retrievers (SRs) in acute ischemic stroke due to large vessel occlusion (LVO). Methods: We reviewed the databases of two comprehensive stroke centers in in Germany and Switzerland for MT due to LVO in the anterior circulation with either ERIC or another SR as a first device. Co-primary outcome was defined as successful recanalization (Thrombolysis in Cerebral Infarction 2b/3) after the first device and favorable outcome (modified Rankin Scale score 0–2) at 90 days' follow-up. Multiple logistic regression analysis was applied to adjust for potential confounders. Results: 183 consecutive patients with stroke were treated with either ERIC (49%) or a SR (51%) as the first device and successful recanalization was seen in 82% and 57%, respectively (P<0.001). Adding SR to futile ERIC recanalization or vice versa increased final recanalization rates (ERIC: 87%, SR: 79%). The use of ERIC as a first device resulted in favorable clinical outcome in 50% compared with 35% when a SR was used (P=0.038), an effect driven by age, stroke severity, presence of carotid-T-occlusion, and general anesthesia and not by the device deployed. Conclusion: The use of ERIC as a first device appeared to be associated with higher rates of successful recanalization and resulted in better functional outcome. However, favorable outcome was not attributable to ERIC. Most importantly, both device types complemented one another and improved final recanalization rates when used successively.